SINTESIS HIDROKSIAPATIT BERPORI CANGKANG KERANG DARA (Tegillarca granosa) MENGGUNAKAN PATI SINGKONG - lia anggresani (JURNAL KATALISATOR, 2022)
Bone is an important support for the human body and is hard. To overcome damaged tissue, biomaterials can be used by implanting them into bone tissue. The material that can be used as a substitute for bone tissue is hydroxyapatite. The aim of this research was to synthesize porous hydroxyapatite from Clamshells using cassava starch polymer. In this research method, initially, CaO powder was obtained from clamshells in a furnace at a temperature of 800ºC for 3 hours after which XRF analysis was carried out. Next, the CaO powder was reacted with (NH4)2HPO4 with ratio mol Ca/P 1.67 and the pH was adjusted with NaOH to 12. Then, calcinated it at 900ºC, XRD and SEM were analyzed. Hydroxyapatite was mixed with cassava starch polymer with ratio of 10:1 at pH 11 with ammonia stirred at 300 rpm for 5 hours. Next, oven at 110ºC for 5 hours and furnace at 1100ºC about 4 hours. The results of the research were analyzed by XRD, FTIR, SEM, and Compressive Strength Test. XRD analysis on 1,67 mole Ca/P obtained hydroxyapatite compound according with ICSD No. 01-072-124. FTIR analysis shows the functional groups of O-H, P-O, and C-O. SEM analysis obtained particles in the form of non-uniform lumps. The compressive strength of HAp and porous HAp was obtained at 14.58 & 49.20 Mpa. This research concluded that porous hydroxyapatite from clam shells can be made from cassava starch polymer with good strength.